Impact of knowledge / innovation on merger and acquisition success in the pharmaceutical industry: The case of AstraZeneca/Ardea Biosciences and GlaxoSmithKline/Human Genome Sciences - Havard, Victor (2017)
Innovation is a key determinant of performance and competitive advantage. However, firms find it more and more difficult to remain innovating in an increasingly complex knowledge base economy. To counter this difficulty, this paper show that it is key for firms to be able to integrate external knowledge through open innovation. This open innovation is characterized by an increasing number of partnership and merger/acquisition (M&A). The high rate of failure of M&A since 1990 create a problem for firms to manage an efficient open innovation strategy and therefore, interested us to consider the key factors of success of merger and acquisition. A multidisciplinary literature review of M&A key factors of success will highlight the current state of knowledge as well as gaps still existing around this subject. Through our case study composed of two major mergers (AstraZeneca/Ardea Biosciences and GlaxoSmithKline/Human Genome Sciences) in the context of the pharmaceutical industry, we introduce the variable of knowledge structure to further explain M&A success. Findings suggest that the knowledge structure do have an impact on innovation level post-merger and on the overall performance of the firm.